Análisis financiero a los estados financieros de la empresa transportes y servicios asociados “SYTSA Cia Ltda”, de la ciudad de Quito, provincia de Pichincha, correspondiente al periodo 2014 y 2015 - Aguinda Grefa, Guadalupe Soledad (2018)
The present investigative work was developed in order to publicize the economic and financial situation of the company, allowing the Manager to make appropriate decisions for the benefit of the same. It is framed within the parameters established in the corresponding Academic Regulations of the National University of Loja, prior to obtaining the Degree in Accounting and Auditing. This process was achieved by efficiently applying the analysis techniques; In order to meet the specific objectives, we proceeded to determine the degree of participation of each one of the Financial Statements accounts in relation to the group and subgroup to which they belong, getting to know the economic and financial structure in Vertical and Horizontal form, followed by a comparative analysis to establish the increases and decreases that the accounts have had from one period to another as a result of the operations carried out in 2014 and 2015 in the same way the Financial Indicators were applied, to know the economic and financial activity of the Company and thus be able to evaluate the performance of the same, then the easily understandable report was prepared for the Manager and managers in which the results of the analysis and situation were presented in which the Company is currently Transport and Associated Services "Sytsa Cia Ltda " With the obtained results it was possible to determine that the entity is financially and economically stable, it is recommended to perform Financial Analysis periodically, as well as to apply indicators that will help the correct decision making in benefit of the company and therefore achieve the permanence of the company, these alternatives will serve as a guide to managers and partners in decision making.